Performance, durability and recycling of thermoplastic biocomposites reinforced with coriander straw. (October 2018) - Uitterhaegen, E.; Parinet, J.; Labonne, L.; Mérian, T.; Ballas, S.; Véronèse, T.; Merah, O.; Talou, T.; Stevens, C.V.; Chabert, F.; Evon, Ph.
Abstract: In this study, coriander straw fiber was effectively incorporated as a reinforcing filler in polypropylene and biobased low-density polyethylene composite materials through twin-screw extrusion compounding and injection molding. Maleic anhydride-grafted copolymers were added as a coupling agent and effectively provided fiber/matrix compatibilization. With a significant reinforcing effect, resulting in a 50% increase in the flexural and tensile strength (from 19 to 28 MPa and from 12 to 17 MPa, respectively, for polypropylene composites) as compared to the native polymer, coriander straw allowed the production of 40% filled thermoplastic biocomposites with adequate mechanical properties comparable to those of commercial wood fibers, excellent durability in terms of UV and hygrothermal weathering and high potential for recycling. At the same time, such coriander biocomposites show a favorable cost structure, with 28% reduction of the granule cost as compared to wood fiber composites.